Diffuse interstitial lung disease due to AA amyloidosis. Issue 4 (April 1992) - Planes, C; Kleinknecht, D; Brauner, M; Battesti, J P; Kemeny, J L; Valeyre, D
Abstract : A man developed interstitial lung disease and nephrotic syndrome due to AA amyloidosis. There was no evidence of an underlying disease predisposing to amyloidosis.